Summanen, a new meteorite impact structure in Central Finland - Plado, Jüri; Hietala, Satu; Kreitsmann, Timmu; Lerssi, Jouni; Nenonen, Jari; Pesonen, Lauri J. (Meteoritics & Planetary Science, 2020)
The Summanen structure (62 degrees 39.0'N, 25 degrees 22.5'E) is located within the Paleoproterozoic Central Finland Granite Belt, Fennoscandian Shield. The structure is hidden under Lake Summanen and not directly observable. It owes its discovery to low-altitude airborne geophysical data, which revealed a circular, similar to 2.6 km wide electromagnetic in-phase, and resistivity, anomalies. Two field campaigns were conducted in 2017 to search for impact signatures. The fieldwork concentrated on the southeastern side of the lake following the ice flow direction of the latest (Weichselian) glaciation. In addition, the islands and the SE peninsulas of the mainland were investigated for outcrops and glacial erratics. A few tens of erratic boulders with shatter cones and striated features, and a few brecciated rocks were discovered. Lamposaari Island in the eastern part of the lake revealed one fractured outcrop containing in situ porphyritic granite with converging striated features. Microscopic shock metamorphic features in two shatter-cone-bearing samples of porphyritic granite were found. These are planar deformation features (PDFs; up to two sets) in quartz and kink bands in biotite. Based on these geological, geophysical, and petrographic results, we suggest that Lake Summanen hides a relatively small, probably simple, meteorite impact structure, the twelfth confirmed one in Finland, of so far unknown age. Peer reviewed